ANALISA PENGARUH KEPEMIMPINAN TERHADAP KUALITAS KERJA KARYAWAN PT. BANK MAYORA - Sendianto Sendianto; Bambang Ermansyah Saragih; Hendri Hendri (Equilibrium Point : Jurnal Manajemen dan Bisnis, 2022)
Companies in carrying out their business activities need to pay attention to internal and external aspects. Leadership is one of the internal aspects that affect the behavior of a company in carrying out business activities. Performance or performance is the result of work that can be achieved by a person or group of people in the organization, in accordance with their respective authorities and responsibilities. Quality of work is a result that can be measured by the effectiveness and efficiency of a job done by human resources or other resources in achieving the goals or objectives of the company well and efficiently. This shows that the leadership process is the main indicator in improving the quality of work of the employees themselves. The problem is that there is still a lack of harmony between superiors and subordinates and the lack of leadership styles in several companies, causing the performance or quality of work of employees to be disrupted and have a direct impact on the company. Based on this background, the research title "Analysis of the Influence of Leadership on the Quality of Work of PT. Mayora Bank.The results of the simple linear regression analysis of the correlation/relationship (R) summary model are 0.876. From the output, the coefficient of determination (R Square) is 0.767, which means that the influence of the independent variable (Leadership) on the dependent variable (Quality of Work of Employees) is 76.7% and the results of the T test show that the significance for the effect of X on Y is 0.000 0.05 and the t value is 10.581 t, so it can be seen that Ha is accepted and Ho is rejected, H1 is accepted and H2 is rejected. The conclusion of these results proves that there is a large influence and has a close relationship between leadership factors on the quality of work of employees of PT. Mayora Bank.Keywords: Leadership, Quality of Work